2.3k views
1 vote
Let f(x)=3x+2 and g(x)=x+4

Solve:

f(3)

g(-1)

2f(x)

f(x)+g(x)

f(x)-g(x)

f(x)•g(x)

2 Answers

5 votes

f(x) = 3x + 2; g(x) = x + 4

f(3) = 3(3) + 2 = 9 + 2 = 11

g(-1) = -1 + 4 = 3

2f(x) = 2(3x + 2) = (2)(3x) + (2)(2) = 6x + 4

f(x) + g(x) = (3x + 2) + (x + 4) = (3x + x) + (2 + 4) = 4x + 6

f(x) - g(x) = (3x + 2) - (x + 4) = 3x + 2 - x - 4 = (3x - x) + (2 - 4) = 2x - 2

f(x) · g(x) = (3x + 2)(x + 4) = (3x)(x) + (3x)(4) + (2)(x) + (2)(4)

= 3x² + 12x + 2x + 8 = 3x² + 14x + 8

User Reece Kenney
by
5.1k points
2 votes

Answer:

11.

3.

6x+4.

4x+6.

2x-2.

3
x^(2) +14x+8.

Explanation:

f(3) = 3(3)+2 = 9+2 = 11.

g(-1)= -1+4 = 3.

2f(x) = 2(3x+2) = 6x +4.

f(x)+g(x) = 3x+2+x+4 = 4x+6.

f(x)-g(x)= 3x+2 -(x+4) = 3x+2-x-4 = 2x-2.

f(x)*g(x)= (3x+2)(x+4)= 3
x^(2) + 12x+2x+8 = 3
x^(2) +14x+8.

User Ctholho
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.